Modernization of Power System of the Republic of Belarus as Element of Power Saving Conception and Increase in Usage of Own Fuel and Energy Resources - S. P. Tkachyov; V. I. Timoshpolsky; А. V. Ageev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper shows main development directions of power complex of the Republic of Belarus for the period of 2006-2010 that ensure power safety and country’s independence in energy. A special attention is paid to modernization of the main power system funds with the purpose to provide reliable operation and continuous power supply of the national economy.